Measurements of an elliptic pipe jet - Vibhas Pahuja (2014)
This study presents the findings of the mean velocity, Reynolds normal stresses and Reynolds shear stresses for a fully developed pipe jet emanating from a smooth, elliptic pipe of length 999 m and a nozzle exit of aspect ratio (AR) 2:1 (50 mm by 25 mm). The jet flow is fully developed and turbulent in nature. The lack of published studies on the topic of elliptic pipe jets and the effects of initial conditions on non-circular jets provide the main motivation for undertaking this study.